On the theoretical vibration analysis of the exhaust system - Abu, Aminudin (Faculty of Mechanical Engineering, UTM, 1996)
This paper postulates the first stage in the design analysis of an exhaust system. With the specified properties of the material, the exhaust system is modelled by using a conventional FEM package, MSC/NASTRAN. The results are compared to the one developed by Transfer Matrix Method. The hanger location of the exhaust system is determined by estimation of the normal mode of the total exhaust system.